K.C. Mehta and Manoranjan Mitra Award - Present scenario of important fungal diseases of grapes and their management - RAWAL, R.D. (Indian Phytopathology, 2013)
I convey my gratitude to IPS for selecting me to write in honour of great Plant Pathologists. During the past three decades, grape cultivation has become most popular among the fruit growers in Andhra Pradesh, Karnataka, Maharashtra, Tamil Nadu, Punjab, Uttar Pradesh and Haryana, because of higher yields and better monetary returns. At the same time grapevines are susceptible to many diseases, a few of which namely downy mildew, anthracnose and powdery mildew have become limiting factors in its profitable cultivation. It has become necessary to control these diseases every year. The vines are also subjected to several other biotic and abiotic problems, which normally are less serious in nature but occasionally become serious.